PARENTAL MEDIATION EDUCATION PROGRAM FOR TEACHER - Clara Novita Anggraini; Mirah Pertiwi; Yucha Febria Kusumaningrum; Devi Tri Aprilianza; Ocha Trisepta Rachmadiani; Dewa Ayu Aksamala Gangga Paramitha (Charity : Jurnal Pengabdian Masyarakat, 2022)
Still low in cognitive abilities and lack of life experience causes the effects of digital media on children to always be a special concern. With the very dynamic development of technology, every day children can meet a variety of new content. In fact, the character of gadget content is indeed created so that the audience can not stop consuming. The ignorance of parents about this causes addiction to gadget consumption in children is difficult to overcome. As a reference in educating children, the teacher becomes a place to ask questions and help so that children can get away from gadgets. Therefore, it is important for teachers to understand the steps in implementing parental mediation, and the technical way of media education for children at home by parents. The community service team in collaboration with the teacher community held a parental mediation education program. Based on the results of brainstorming problems with partners, this program has the main topics of Parental Mediation, Assertive Communication, and Child Development Tasks. The methods used are webinars, FGDs, and the practice of making reflective writings on understanding the concept of parental mediation. The results of the program are teachers' understanding of the concept of parental mediation. In addition, the recap of the questionnaire shows the satisfaction of the participants in joining the program. Another outcome of this program is the intellectual property rights of the training modules made by the team. This module will be used in sustainability programs in other areas. Keywords: Parental mediation, teacher, digital literacy